2016
DOI: 10.1002/asi.23678
|View full text |Cite
|
Sign up to set email alerts
|

Information management in the humanities: Scholarly processes, tools, and the construction of personal collections

Abstract: The promise and challenge of information management in the humanities has garnered a great deal of attention and interest (Bulger et al., ; Freiman et al., ; Trace & Karadkar, ; University of Minnesota Libraries, ; Wilson & Patrick, ). Research libraries and archives, as well as groups from within the humanities disciplines themselves, are being tasked with providing robust support for information management practices, including helping to engage humanities scholars with appropriate digital technologies in way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…Within the humanities, this work is best embodied by efforts to identify so-called 'scholarly primitives' (Unsworth, 2000) -or the 'basic functions common to scholarly activity across [humanities] disciplines' (Blanke & Hedges, 2013 p. 655) -and translate them into specific infrastructural or technology interventions that facilitate these practices within digital research. Unsworth initially describes several primitives (Discovering, Annotating, Comparing, Referring), which have been expanded and refined by others investigating user experience design and digital tool development (Blanke & Hedges, 2013;Trace & Karadkar, 2017). Other work in web archives has similarly focused on developing 'task models' or 'process models' for big data tools, most recently with the FEAV model (Filter, Extract, Aggregate and Visualize), which was developed in conjunction with the Archives Unleashed Toolkit (Jackson et al, 2016;Lin et al, 2017;Ruest et al, 2020).…”
Section: Developing a Conceptual Frameworkmentioning
confidence: 99%
“…Within the humanities, this work is best embodied by efforts to identify so-called 'scholarly primitives' (Unsworth, 2000) -or the 'basic functions common to scholarly activity across [humanities] disciplines' (Blanke & Hedges, 2013 p. 655) -and translate them into specific infrastructural or technology interventions that facilitate these practices within digital research. Unsworth initially describes several primitives (Discovering, Annotating, Comparing, Referring), which have been expanded and refined by others investigating user experience design and digital tool development (Blanke & Hedges, 2013;Trace & Karadkar, 2017). Other work in web archives has similarly focused on developing 'task models' or 'process models' for big data tools, most recently with the FEAV model (Filter, Extract, Aggregate and Visualize), which was developed in conjunction with the Archives Unleashed Toolkit (Jackson et al, 2016;Lin et al, 2017;Ruest et al, 2020).…”
Section: Developing a Conceptual Frameworkmentioning
confidence: 99%
“…The field remains capacious, embracing information practices such as archiving, quantitative analysis, tool‐building, visualization, 3D modeling, sonification, curation, manipulation, interpretation, editing, modeling, mapping, reading, mining, gaming, remixing, publishing, critiquing, collaborating, code studies, and databases—often at unprecedented scale and scope (Burdick, ; Davidson, ; Hayles, ; Klein & Gold, ; Poole, , ; Trace & Karadkar, ). Often trained in traditional disciplines, DH scholars may occupy traditional faculty positions, but in addition to or instead of these positions, many undertake hybrid information work involving a wide range of digital data, resources, methods, activities, and tools (Clement & Carter, ; Given & Willson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mendeley makes organization and browsing easy as well as the capturing metadata were the most popular items in the category of 'organize your content.' To a great extent, the capture dwells distant from ideal [16]. This research indicated many Mendeley users are importing papers from the existing library.…”
Section: P8mentioning
confidence: 98%